Interaction of chronic intermittent ethanol and repeated stress on structural and functional plasticity in the mouse medial prefrontal cortex. (January 2021) - Cannady, Reginald; Nguyen, Tiffany; Padula, Audrey E.; Rinker, Jennifer A.; Lopez, Marcelo F.; Becker, Howard C.; Woodward, John J.; Mulholland, Patrick J.
Abstract: Stress is a risk factor that plays a considerable role in the development and maintenance of alcohol (ethanol) abuse and relapse. Preclinical studies examining ethanol-stress interactions have demonstrated elevated ethanol drinking, cognitive deficits, and negative affective behaviors in mice. However, the neural adaptations in prefrontal cortical regions that drive these aberrant behaviors produced by ethanol-stress interactions are unknown. In this study, male C57BL/6J mice were exposed to chronic intermittent ethanol (CIE) and repeated forced swim stress (FSS). After two cycles of CIE x FSS, brain slices containing the prelimbic (PrL) and infralimbic (IfL) cortex were prepared for analysis of adaptations in dendritic spines and synaptic plasticity. In the PrL cortex, total spine density was increased in mice exposed to CIE. Immediately following induction of long-term potentiation (LTP), the fEPSP slope was increased in the PrL of CIE x FSS treated mice, indicative of a presynaptic adaptation on post-tetanic potentiation (PTP). In the IfL cortex, CIE exposure regardless of FSS experience resulted in an increase in spine density. FSS alone or when combined with CIE exposure increased PTP following LTP induction. Repeated FSS episodes increased IfL cortical paired-pulse facilitation, a second measure of presynaptic plasticity. In summary, CIE exposure resulted in structural adaptations while repeated stress exposure drove metaplastic changes in presynaptic function, demonstrating distinct morphological and functional changes in PrL and IfL cortical neurons. Thus, the structural and functional adaptations may be one mechanism underlying the development of excessive drinking and cognitive deficits associated with ethanol-stress interactions. Highlights: Chronic ethanol and repeated stress produced distinct morphological and functional changes in the medial prefrontal cortex. Chronic intermittent ethanol exposure increased dendritic spine density. Repeated stress exposure increased the early phase of synaptic plasticity. Chronic stress episodes produced metaplastic changes in presynaptic function.